COUNSELLING FOR PRODUCTIVE EMPLOYMENT - Tambawal, Malami Umar (Sokoto Educational Review, 2020)
This paper discussed the meaning of counselling which is aimed at the personal – social, academic and vocational development of an individual. It further discussed the need for counselling individual student in the area of vocational development and planning, bringing to focus the specific practical aspects of vocational developments. Aspects to be emphasized upon for a result oriented education system for productive employment. The paper concluded by suggesting a marriage between the world of education and the world of work As a way of recommendation, this paper suggested that the curricular of primary and secondary school be fashion out in way that practical skills of local crafts and related trades are incorporated into teaching and learning, also the dignity of labour should be entrenched into the education system and respected.